The influence of digital professional development and professional learning communities in the relationship between school digital preparedness and digital instructional integration. - Stephen Kwashie Amemasor; Stephen Opoku Oppong; Benjamin Ghansah; Ben-Bright Benuwa; Mathias Agbeko (PLoS ONE)
Integration of digital tools and resources in STEM instruction has garnered significant attention due to its high potential. Digital professional development and professional learning communities are identified as a pivotal factor for equipping teachers with the necessary digital skills to effectively orchestrate digital resources. Notably, their role is considered critical. However, the intricate relationships among school digital preparedness, professional learning community, digital professional development, and digital instructional integration among STEM teachers remain underexplored. Utilising partial least-squares-structural equation models (PLS-SEM), the present study examined links in school digital preparedness, professional learning community, digital professional development, and digital instructional integration among STEM teachers (N = 188). Findings from the PLS-SEM analysis indicate that digital professional development and professional learning community exhibit a direct positive relationship with school digital preparedness and digital instructional integration. Relatedly, digital professional development is positively correlated with digital instructional integration. In terms of indirect effect, findings show that professional learning community and digital professional development play a significant positive mediating role in linking digital professional development and digital instructional integration. This study reports new evidence on the influence of school digital preparedness on digital instructional integration through digital professional development among 188 STEM teachers and concludes that, when STEM teachers regularly immerse themselves in digital professional development program, they are more likely to benefit from their digital professional development by integrating digital technologies in classroom instruction. Policymakers and educational leaders should consider promoting digital professional development among STEM teachers, along with efforts to encourage digital instructional integration.